Optimization of Technology for Performing Liquidation Measures at Chemical Weapons Destruction Facilities - V. P. Kapashin; V. G. Mandych; A. Y. Karmishin; I. N. Isaev; A. S. Lyakin; I. V. Kovalenko; V. D. Nazarov (Вестник войск РХБ защиты)
In accordance with the instructions of the President of the Russian Federation, the implementation of the Russian Federation's conventional obligations in the field of chemical disarmament assumes, after the completion of the destruction of chemical weapons, the involvement of former chemical weapons destruction facilities (CWDFs) in the economic turnover in the interests of the industries, connected with defense and state security, and other industries. The aim of this work is to consider the optimal technologies of the destruction of former CWDFs. In order to obtain objective information about the effectiveness and sufficiency of heat treatment of scrap metal products and spent sorbents, potentially contaminated with toxic substances, the FSBE «FUBKHUHO» experts conducted an experimental study of the possibility of using only regular production facilities for thermal neutralization of emptied cases of chemical ammunition and other waste, located at the CWDFs «Maradykovsky», «Leonidovka» and «Pochep». It is established during this study, that the use of standard heat treatment complexes allows to ensure the sanitary and epidemiological safety of the neutralized materials when using their design modes in the temperature range 500–700 °C. This approach allows to reduce the time required for full implementation of liquidation activities at the CWDFs at the expense of the refusal from the creation of new and/or reconstruction of existing facilities of heat treatment, necessary for the neutralization of potentially dangerous fragments of metal constructions and other solid waste, and to increase the efficiency of using financial, material and human resources to ensure the implementation of abandonment operations in general. A timely solution to the problem of the elimination of the consequences of CWDFs' activities will create safe conditions for the development of traditional and new industries on the basis of former CWDF complexes and increase their investment attractiveness.